Analisis Ekonomi Islam Terhadap Peran Perempuan dalam Peningkatan Ekonomi Keluarga Melalui Usaha Batu Bata - Widiaty, Eny (Kartika: Jurnal Studi Keislaman, 2026)
This study aims to analyze the role of women in the brick business in Labuan Tereng Village, West Lombok Regency from an Islamic economic perspective. This study uses a qualitative approach with field research and a normative-empirical design. Research data was obtained through in-depth interviews with 24 female brick workers. Data analysis was conducted using descriptive qualitative methods based on the maqashid Syariah framework, specifically hifz al-mal and hifz al-nafs.The results show that women in Labuan Tereng Village are actively involved in the production process and management of the brick business without neglecting their primary roles in the household. The contribution of women as brick workers has helped increase family income and strengthen household economic resilience amid low husband income. In Islam, the role of women is in accordance with Sharia principles because they have obtained their husbands' permission, maintain moral values, and do not neglect their responsibilities in the family. An analysis of Sharia maqashid shows that women's roles have preserved wealth (hifz al-mal) through increased income and realized family welfare (hifz al-nafs) by achieving maslahah.